2020
DOI: 10.21512/humaniora.v11i1.6363
|View full text |Cite
|
Sign up to set email alerts
|

Reflection on Technology-Enhanced Learning in Research Based Teaching Method Implementation

Abstract: The research aimed to investigate the utilization of technological tools in implementing the research-based teaching method in English for Academic Writing Course. The narrative research design was implemented to reach the conclusion of the research. 66 (sixty-six) students enrolled in English for Academic Writing Course were observed. Lecturer’s reflective journal and portfolios were analyzed. An online interview was conducted to confirm the initial findings. There were six technological tools and application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…They grew up with touch-screens. Putri (2020) in one of her research indicated the use of technological tools in teaching-learning process could help increase students' motivation and enables students to work collaboratively. Her research was done in 2020 where her research aimed to investigate the utilization of technological tools in implementing the researchbased teaching method in English for Academic Writing Course.…”
Section: Resultsmentioning
confidence: 99%
“…They grew up with touch-screens. Putri (2020) in one of her research indicated the use of technological tools in teaching-learning process could help increase students' motivation and enables students to work collaboratively. Her research was done in 2020 where her research aimed to investigate the utilization of technological tools in implementing the researchbased teaching method in English for Academic Writing Course.…”
Section: Resultsmentioning
confidence: 99%
“…Teachers' participation in monitoring student assignments' completion also plays a vital role in developing students' speaking skills. With collaborative skills, students can increase motivation and student learning involvement in learning activities outside the classroom (Putri, 2020).…”
Section: (Xuéhǎo Yī Mén Yǔyán Xūyào____________ Zhèyàng Cáinéng Xuéhǎo)mentioning
confidence: 99%
“…Technological developments inevitably provide opportunities for art people to more efficiently market their work to the public with the aim of being a means of publication. Therefore, through a short dance filmmaking project, this course is possible to lift the image of the institution in the context of arts and also provide space for students to do creativity independently with a collaborative model (Putri, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The second is collaborative skills, such as reasoning, which are students' ability to work with others. Collaborative skills allow students to improve the quality of learning (Indriwati, Susilo, & Hermawan, 2019;Putri, 2020). These skills are a vehicle for students to learn to have collaborative skills.…”
Section: Introductionmentioning
confidence: 99%